A novel role of the splenic volume in Crohn’s disease: evaluating the efficacy of infliximab - Shi, Xuan; Wang, Jia-Hui; Rao, Sheng-Xiang; Liu, Tao-Tao; Wu, Hao (Frontiers in Pharmacology, 2023)
Background: A number of patients with Crohn's disease (CD) suffer from loss of response to infliximab (IFX) therapy. Splenic volume is reported to be enlarged in patients with CD compared to normal individuals. Whether the splenic volume is associated with IFX efficacy in CD remains unclear.We performed a retrospective study of patients with CD who received regular IFX treatment at Zhongshan Hospital, Fudan University between August 2015 and December 2021. We collected baseline characteristics and clinical features from medical records in the CD database of Zhongshan Hospital. We accurately measured splenic volume through using semi-auto spleen segmentation software, followed by the analysis of splenic volume and IFX efficacy.We included 49 patients with CD receiving IFX treatment, of whom 41 responded to IFX and 8 failed to respond to IFX. Splenic volume, as well as volume adjusted for body mass index (SV/BMI) and body weight (SV/W), were significantly decreased after IFX treatment in responders, while increased in non-responders, compared to the volume before the treatment. Accordingly, there were downregulation levels of leukocyte count, platelet count, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) after IFX treatment in responders. Contrarily, hemoglobin, albumin, and tumor necrosis factor (TNF)-α levels were elevated in responders.Moreover, both CRP and TNF-α levels were significantly positively correlated with SV/BMI in all patients.Conclusions: Splenic volume, especially SV/BMI and SV/W, were reduced after IFX treatment in CD patients responsive to IFX. SV/BMI was positively correlated with disease activity. Splenic volume is a promising indicator to evaluate IFX efficacy in CD.